A Multifunctional MnII Phosphonate for Rapid Separation of Methyl Orange and Electron‐Transfer Photochromism. Issue 33 (4th July 2016) - Gao, Chao‐Ying; Yang, Yang; Ai, Jing; Tian, Hong‐Rui; Li, Lei‐Jiao; Yang, Weiting; Dang, Song; Sun, Zhong‐Ming
Abstract: A Mn II phosphonate of the general formula [Mn(H2 L)2 (H2 O)2 (H2 bibp)] adopts a layered motif with protonated H2 bibp 2+ cations embedded in the channels (H4 L=thiophene‐2‐phosphonic acid; bibp=4, 4′‐bis(1‐imidazolyl)biphenyl). The title compound exhibits excellent adsorptive removal of methyl orange (MO) dye from aqueous solution. Its advantageous features include fast adsorption, high uptake capacity, selective removal, and reusability, which are of great significance for practical application in wastewater treatment. Meanwhile, the compound displays rapid photochromism upon irradiation with visible light at room temperature. Extensive research has demonstrated that such behavior is based on a ligand‐to‐ligand charge‐transfer (LLCT) mechanism. The irradiated sample possesses an ultra‐long‐lived charge‐separated state. Moreover, not only is the compound the first Mn‐based photochromic MOF, but it is also one of the very few examples showing LLCT with non‐photochromic components. Abstract : Versatile metal–organic framework : A Mn II phosphonate has been shown to be an excellent adsorbent for the rapid separation of methyl orange (MO) dye from aqueous solution (see figure), having the advantages of rapid adsorption rate, high uptake capacity, and good recovery of raw materials. Interestingly, it also displays visible‐light‐induced photosensitive behavior, and a ligand‐to‐ligand electron‐transfer mechanism has been proposed to rationalize its photochromic phenomena.